Emprego de nebulizador pneumático de ICP-MS como câmara de diluição em sistemas de injeção em fluxo para determinações multielementares - Gomes Neto, José Anchieta [UNESP]; Silva, José Bento B.; Rodrigues Neto, Renato; Curtius, Adilson José; Souza, Ivan G. (Sociedade Brasileira de Química, 1998)
An automatic dispenser based on a flow-injection system used to introduce sample and analytical solution into an inductively coupled plasma mass spectrometer through a spray chamber is proposed. Analytical curves were constructed after the injection of 20 to 750 µL aliquots of a multielement standard solution (20.0 µg L-1 in Li, Be, Al, V, Cr, Mn, Ni, Co, Cu, Zn, As, Se, Sr, Ag, Cd, Ba, Tl, Pb) and the acquisition of the integrated transient signals. The linear concentration range could be extended to ca. five decades. The performance of the system was checked by analyzing a NIST 1643d reference material. Accuracy could be improved by the proper selection of the injected volume. Besides good precision (r.s.d. < 2%), the results obtained with the proposed procedure were closer to the certified values of the reference material than those obtained by direct aspiration or by injecting 125 µL of several analytical solutions and samples.
Pneumatic nebulizer as a dilution chamber in a flow-injection system for multielement analysis by ICP-MS
Keywords: pneumatic nebulizers; ICP-MS; on-line dilution